Investigate the genetic mechanisms of diabetic kidney disease complicated with inflammatory bowel disease through data mining and bioinformatic analysis - Zhang, Xiaoyu; Xiao, Huijie; Fu, Shaojie; Yu, Jinyu; Cheng, Yanli; Jiang, Yang (Frontiers in Endocrinology, 2023)
Background： Patients with diabetic kidney disease (DKD) often have gastrointestinal dysfunction such as inflammatory bowel disease (IBD). This study aims to investigate the genetic mechanism leading to IBD in DKD patients through data mining and bioinformatics analysis. Methods: The disease-related genes of DKD and IBD were searched from the five databases of OMIM, GeneCards, PharmGkb, TTD, and DrugBank, and the intersection part of the two diseases were taken to obtain the risk genes of DKD complicated with IBD. A protein-protein interaction (PPI) network analysis was performed on risk genes, and three topological parameters of degree, betweenness and closeness of nodes in the network were used to identify key risk genes. Finally, Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were performed on the risk genes to explore the related mechanism of DKD merging IBD. Results: This study identified 495 risk genes for DKD complicated with IBD. After constructing a protein-protein interaction network and screening for 3 times, 6 key risk genes were obtained, including MMP2, HGF, FGF2, IL-18, IL-13 and CCL5. Based on GO enrichment analysis, we found that DKD genes complicated with IBD were associated with 3646 biological processes such as inflammatory response regulation, 121 cellular components such as cytoplasmic vesicles, and 276 molecular functions such as G protein-coupled receptor binding. Based on KEGG enrichment analysis, we found that the risk genes of DKD combined with IBD were associated with 181 pathways, such as the PI3K-Akt signaling pathway, AGE-RAGE signaling pathway and HIF-1 signaling pathway. Conclusion: There is a genetic mechanism for the complication of IBD in patients with CKD. Oxidative stress, chronic inflammatory response, and immune dysfunction were possible mechanisms for DKD complicated with IBD.